Applicability of the melanger for chocolate refining and Stephan mixer for conching as small-scale alternative chocolate production techniques. (July 2019) - Hinneh, Michael; Van de Walle, Davy; Haeck, Julie; Abotsi, Enoch Enorkplim; De Winne, Ann; Saputro, Arifin Dwi; Messens, Kathy; Van Durme, Jim; Afoakwa, Emmanuel Ohene; De Cooman, Luc; Dewettinck, Koen
Abstract: Conventional dark chocolate production methods that are applied in the industry consist of several steps, which require equipment with big investment costs. There are however few cost-effective alternatives suggested for small-scale production. Meanwhile, knowledge on these alternative equipment/techniques are insufficient to promote miniature production of high quality chocolates, either for research purposes in an industrial context, or for producers in developing countries, where the cost of investing in conventional equipment seems to be an impediment. The aim of this study was two-fold; first, to assess the feasibility of utilizing the ECGC-12SLTA CocoaTown melanger as an alternative to the conventional 3-roll refiner at different settings and fat content. Thereafter, one optimal setting was selected for each equipment for further investigation on the impact of the refining on some quality attributes of the final dark chocolate (70% cocoa). Secondly, the Stephan mixer; being used to mimick a conching-like process, was assessed with respect to two processing factors; the dry conching temperature (60 °C, 80 °C) and the duration of vacuum pump connection (0, 30, 60 min). The latter was to facilitate adequate moisture removal. The melanger proved to be a suitable alternative to the 3-roll refiner, provided that refining was carried out at moderate/high (ca. 40%) fat content, as is often the case for "high-percentage-cocoa" chocolates. Refining for 180 min with the mini drum at 40% resulted in D (v, 0.9) significantly (p < 0.05) lower than when the 3-roll refiner was used. Nonetheless, a comparative advantage of the latter would be its short throughput time (5–10 min). Due to a resultant linear speed gradient of the chocolate mass due to the cylindrical roller stones, a more efficient refining was achieved with the mini drum than with the big drum. More so, refining in excess fat (40%) may have contributed to a more efficient coating of the newly created hydrophilic sugar surfaces, thus, limiting the possibility for moisture-induced agglomeration as may have been the case for the recipe with 27% fat. In spite of trivial difference in moisture content, chocolates manufactured following melanger and 3-roll refining showed significant (p < 0.05) differences in terms of particle size, flow parameters and color. For chocolates that were conched with the Stephan mixer, the vacuum duration had a significant (p < 0.05) impact on moisture content and D (v, 0.9). Also, an impact of all factors and their interaction on the Casson yield values of the chocolates was observed. However, these factors proved to be less important in dictating the final viscosities of the chocolates. Among others, it is suggested that the influence of the high fat content of the chocolates may have played a more important role. Although all chocolates exhibited less thixotropic behavior, a direct proportional relationship between the particle surface area and thixotropy was observed. Finally, the interaction effect of both factors also significantly (p < 0.05) influenced the color of the chocolates. Highlights: A minimum refining duration of 180 min was required for melanger (mini drum) to attain particles lower than 3-roll refiner. Except for moisture, different refining techniques showed significant impact on various chocolate quality attributes. Except for viscosity, impact of conching temperature and vacuum duration were seen on various chocolate quality attributes.